2005
DOI: 10.1371/journal.pmed.0020345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Prediction of Future Type 2 Diabetes

Abstract: BackgroundType 2 diabetes (T2D) is a multifactorial disease in which environmental triggers interact with genetic variants in the predisposition to the disease. A number of common variants have been associated with T2D but our knowledge of their ability to predict T2D prospectively is limited.Methods and FindingsBy using a Cox proportional hazard model, common variants in the PPARG (P12A), CAPN10 (SNP43 and 44), KCNJ11 (E23K), UCP2 (−866G>A), and IRS1 (G972R) genes were studied for their ability to predict T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 43 publications
4
101
2
Order By: Relevance
“…A common glutamate (E) 3 lysine (K) change at position 23 (E23K) has been consistently associated with type 2 diabetes, with an overall allelic odds ratio (OR) near 1.15 (2)(3)(4)(5)(6)(7)(8)(9) for the comparison of diabetic individuals with nondiabetic control subjects. Moreover, we and others (5,8,10) have shown that normoglycemic lysine carriers consistently display a defect in insulin secretion. In vitro, the lysine risk allele seems to affect potassium channel properties (11,12).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…A common glutamate (E) 3 lysine (K) change at position 23 (E23K) has been consistently associated with type 2 diabetes, with an overall allelic odds ratio (OR) near 1.15 (2)(3)(4)(5)(6)(7)(8)(9) for the comparison of diabetic individuals with nondiabetic control subjects. Moreover, we and others (5,8,10) have shown that normoglycemic lysine carriers consistently display a defect in insulin secretion. In vitro, the lysine risk allele seems to affect potassium channel properties (11,12).…”
mentioning
confidence: 52%
“…The Finnish Diabetes Prevention Study (14) randomized 522 subjects with impaired glucose tolerance (IGT) to either placebo or a lifestyle intervention and found that lysine carriers at KCNJ11 E23K appeared more likely to develop diabetes over time than E/E homozygotes, although the difference was not statistically significant. In contrast, the larger Botnia Prospective Study (10) suggested that the lysine allele was protective, although, again, this effect was not statistically significant. Whether statistical fluctuations or differences in ascertainment schemes (IGT vs. a population sample) and analytical methods (logistic regression vs. Cox proportional hazards analysis) explain these discrepancies is not yet clear.…”
mentioning
confidence: 81%
“…Lyssenko et al showed that the Pro12Pro genotype in PPARG predicted future T2D in individuals with BMI  30 kg/m 2 and fasting plasma glucose > 5.5 mmol/l with an OR of 1.7 (31). The TT risk genotype of SNP 44 in CAPN10 increased this risk in an additive manner to an OR of 2.7.…”
Section: Genetic Prediction Of Type 2 Diabetesmentioning
confidence: 99%
“…A common variant, Glu23Lys, of the Kir6.2 subunit (KCNJ11) was the first naturally occurring variant of Kir6.2 in vitro that was found to induce a hyperactive state of the K ATP channel complex (7) and reducing its sensitivity to the inhibitory action of ATP. In healthy subjects, the Glu23Lys variant associates with an impaired post glucose-load release of insulin (8,9) and with a weaker suppression of glucagon secretion in response to hyperglycaemia (10). It has therefore been speculated that this reduction in b-cell function and increased a-cell activity in Glu23Lys carriers may explain the association of this variant with type 2 diabetes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes is characterised by the progressive loss of insulin producing b-cells due to an autoimmune attack, and is estimated to retain 10% of the b-cell mass at the time of diagnosis (12). In parallel with the effect in impaired b-cell function (8,9), the Glu23Lys variant also seems to have an effect on a-cell function (10). But as glucagon secretion from the a-cells may effectively be regulated by an intraislet paracrine insulin release from the b-cells, it is not possible to distinguish the effect of Glu23Lys in primary defective a-cell function from an indirect effect caused by impaired intraislet insulin release.…”
Section: Introductionmentioning
confidence: 99%